Antimicrobial activity and metabolite profiling of lactic acid bacteria isolated from solid and liquid tofu waste - RYAN MOULANA; YULIA SARI ISMAIL; DEWI YUNITA; DALLYA IZLA; CUT YULVIZAR (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Moulana R, Ismail YS, Yunita D, Izla D, Yulvizar C. 2026. Antimicrobial activity and metabolite profiling of lactic acid bacteria isolated from solid and liquid tofu waste. Biodiversitas 27 (6): d270621. https://doi.org/10.13057/biodiv/d270621. The production of tofu generates two types of waste by-products: solid (tofu pulp) and liquid (tofu whey). These by-products are rich in carbohydrates and proteins, which can support the growth of lactic acid bacteria (LAB). The objective of this study was to isolate and phenotypically characterize presumptive LAB isolates from tofu waste and to evaluate their antimicrobial activity against Escherichia coli, Staphylococcus aureus, and Candida albicans. Presumptive LAB were isolated using De Man, Rogosa, and Sharpe (MRS) agar supplemented with 1% CaCO₃ and phenotypically characterized based on Gram-positive reaction, catalase-negative activity, and cocci or rod-shaped cell morphology. Antimicrobial activity was evaluated using the disc diffusion method with cell-free supernatants (CFS) as a preliminary antimicrobial screening approach. The results showed that eight presumptive LAB isolates were obtained, consisting of three isolates from solid tofu waste (LPT1-LPT3) and five from liquid tofu waste (LCT1-LCT5). LPT1 demonstrated the largest inhibition zone against S. aureus (12.77 mm; strong category), while LCT1 exhibited the largest inhibition against E. coli (7.26 mm; moderate category). However, no antifungal activity was detected against C. albicans. GC-MS metabolite profiling of isolates LPT1 and LCT1 identified 18 chemical compounds, with acetic acid detected as the dominant metabolite in both isolates. These findings indicate that LAB isolated from tofu waste may represent a potential source of antimicrobial metabolites. However, further quantitative and molecular analyses are required to clarify the contribution of specific metabolites to the observed antibacterial activity.